Phospholipase C-β3 regulates FcεRI-mediated mast cell activation by recruiting the protein phosphatase SHP-1 - Xiao, Wenbin (2011)
Mast cells are major effectors in high-affinity IgE receptor (FcεRI)-dependent allergic reactions. Here we show that phospholipase C (PLC)-β3 is crucial for FcεRI-mediated mast cell activation. Plcb3(−/−) mice showed blunted FcεRI-dependent late-phase, but not acute, anaphylactic responses and airway inflammation. Accordingly, FcεRI stimulation of Plcb3(−/−) mast cells exhibited reduced cytokine production, but normal degranulation. Reduced cytokine production in Plcb3(−/−) cells could be accounted for by increased activity of the negative regulatory Src family kinase Lyn and reduced activities of the positive regulatory protein kinases MAPKs. Mechanistically, PLC-β3 constitutively interacts with FcεRI, Lyn and SHP-1 (protein phosphatase). SHP-1 likely recognizes its substrates Lyn and MAPKs via the recently described kinase tyrosine-based inhibitory motif, KTIM. Consistent with PLC-β3- and SHP-1-mediated repression of Lyn activity by dephosphorylation at Tyr(396), FcεRI-mediated phenotypes were similar in Plcb3(−/−) and SHP-1-mutant mast cells. Thus, we have defined a PLC-β3- and SHP-1-mediated signaling pathway for FcεRI-mediated cytokine production.